2013
DOI: 10.1603/me12064
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Resistance in Two <I>Aedes aegypti</I> (Diptera: Culicidae) Strains From Costa Rica

Abstract: Dengue (family Flaviridae, genus Flavivirus, DENV) and dengue hemorrhagic fever (DHF) are presently important public health problems in Costa Rica. The primary strategy for disease control is based on reducing population densities of the main mosquito vector Aedes aegypti (L.) (Diptera: Culicidae). This is heavily dependent on use of chemical insecticides, thus the development of resistance is a frequent threat to control program effectiveness. The objective of this study was to determine the levels of insecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 18 publications
3
52
2
2
Order By: Relevance
“…Effects similar to the fi ndings presented in this study have been found in various assays showing synergism between low concentrations of PBO and organophosphates in insect species 14,15,20,24,25 . The high level of synergism of 1% PBO in the larvicidal effect of TE has important implications for the control of A. aegypti larvae.…”
Section: Effects Of Pbo On Esterase Activitysupporting
confidence: 89%
See 2 more Smart Citations
“…Effects similar to the fi ndings presented in this study have been found in various assays showing synergism between low concentrations of PBO and organophosphates in insect species 14,15,20,24,25 . The high level of synergism of 1% PBO in the larvicidal effect of TE has important implications for the control of A. aegypti larvae.…”
Section: Effects Of Pbo On Esterase Activitysupporting
confidence: 89%
“…According to this hypothesis, at 2%, the effects of isomers responsible for the bioactivation of TE increased, offsetting the effect of the isomers involved in metabolic detoxifi cation [18][19][20][21][22] .…”
Section: Effects Of Pbo On Esterase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti was susceptible to it. 13 In this study, Ae. aegypti mosquitoes showed resistance to Lambda-cyhalothrin and DDT, a result which was similarly obtained by other authors in India 11 with the exception only to the susceptibility of Ae.…”
Section: Adult Susceptibilitymentioning
confidence: 86%
“…aegypti larvae showed higher resistance levels to the organophosphate (OP) temephos and the adult were resistant to deltamethrin, but susceptible to bendiocarb, chlorpyrifos, and cypermethrin. 13 In Havana city, a high resistance of Ae. aegypti larvae to temephos and fenthion was observed.…”
mentioning
confidence: 99%